2023
DOI: 10.1177/27536130221147475
|View full text |Cite
|
Sign up to set email alerts
|

Cereset Research Standard Operating Procedures for Insomnia: A Randomized, Controlled Clinical Trial

Abstract: Background Interventions for insomnia that also address autonomic dysfunction are needed. Objective We evaluate Cereset Research™ Standard Operating Procedures (CR-SOP) in a pilot randomized, controlled trial. CR-SOP is a less operator-dependent, more generalizable innovation of HIRREM®, a noninvasive, closed-loop, allostatic, acoustic stimulation neurotechnology demonstrated to improve insomnia and autonomic function. Methods Adults with Insomnia Severity Index (ISI) scores of ≥8 were randomized to receive te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 47 publications
(73 reference statements)
1
7
0
Order By: Relevance
“…The intervention group in both studies also demonstrated clinically relevant improvement, whereas the sham groups did not. In the CR‐SOP insomnia study, not only did sleep quality improve, but some measures of autonomic function improved significantly among the intervention group compared to control 31 . These studies, taken with the results of the current study, suggest the impact of the common elements between the allocation groups, notably 10 h of relaxation facilitated by a zero gravity chair and computer‐generated auditory tones, shows statistically significant changes from pre‐intervention.…”
Section: Discussionsupporting
confidence: 66%
See 4 more Smart Citations
“…The intervention group in both studies also demonstrated clinically relevant improvement, whereas the sham groups did not. In the CR‐SOP insomnia study, not only did sleep quality improve, but some measures of autonomic function improved significantly among the intervention group compared to control 31 . These studies, taken with the results of the current study, suggest the impact of the common elements between the allocation groups, notably 10 h of relaxation facilitated by a zero gravity chair and computer‐generated auditory tones, shows statistically significant changes from pre‐intervention.…”
Section: Discussionsupporting
confidence: 66%
“…The fact that the overall study population showed such marked and sustained improvement indicates that study participation, which included relaxation via resting in a comfortable, zero‐gravity chair with eyes closed in dim light while listening to engineered auditory tones, is therapeutic. Two previously published studies evaluating legacy HIRREM 30 and CR‐SOP 31 for insomnia found improvement in both allocation groups, though the active intervention group had statistically significant larger improvement than the sham group. The intervention group in both studies also demonstrated clinically relevant improvement, whereas the sham groups did not.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations